Implementation of Hydroponic Technology to Strengthen Household Food Security in Urban Marginal Areas - Abadi, Satria; Jatiningrum, Citrawati; Gumanti, Miswan; Kristina, Marilin (Journal Ligundi of Community Service, 2025)
Background. Urban marginal areas often face limited access to arable land and high dependency on fluctuating food markets, which weakens household food security. Hydroponic technology, as a soilless cultivation method, offers an innovative approach to optimize limited space while ensuring sustainable food production. The implementation of hydroponics in household settings is increasingly viewed as a potential solution to reduce food vulnerability and enhance nutritional self-sufficiency. Purpose. This study aimed to examine the role of hydroponic technology in strengthening household food security among families in urban marginal areas. Specifically, it explored how hydroponic practices contribute to increasing food availability, reducing household food expenses, and promoting community resilience. Method. The research employed a mixed-method design involving surveys and focus group discussions with 120 households implementing hydroponic systems across selected urban marginal areas. Quantitative data from household food security indicators were analyzed using statistical techniques, while qualitative insights were obtained to understand the practical challenges and opportunities of hydroponic adoption. Results. The findings indicate that hydroponic technology significantly contributes to household food availability, with participants reporting reduced dependence on external food sources and improved dietary diversity. Additionally, households noted a decline in monthly food expenditures, although initial setup costs were perceived as a barrier. Qualitative data highlighted that training, community collaboration, and institutional support are crucial for successful hydroponic adoption in marginalized contexts. Conclusion. The implementation of hydroponic technology plays a vital role in strengthening household food security in urban marginal areas. By integrating hydroponics into household practices, families can achieve greater food self-reliance and resilience. These results underscore the importance of policy support, community-based programs, and financial assistance to maximize the scalability and sustainability of hydroponic initiatives.